2022
DOI: 10.1002/agj2.21101
|View full text |Cite
|
Sign up to set email alerts
|

Spring wheat yield and grain quality response to nitrogen rate

Abstract: Nitrogen (N) is the most limiting nutrient in cereal production, yet its use efficiency remains very low at only 35%. Nutrient use efficiency (NUE) is crucial for increasing crop yield and quality while reducing fertilizer inputs and minimizing environmental damage. Optimum N rates that maximize yield without reducing NUE have been found to vary from location to location. This field study assessed the effect of N rates on the yield and quality of spring wheat (Triticum aestivum L.) at five locations in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Higher doses of nitrogen fertilization had a positive effect on all elements of the yield structure, increasing the number of ears, ear fertility, and grain abundance. It was also confirmed by the results of numerous studies, which indicate that long-term N fertilization can contribute to relieving the global food crisis by not only enhancing cereal yield, but also promoting its stability [44,45]. Mohammed et al [46] also observed the beneficial effect of an increase in fertilizer N rates in wheat grain yield and protein content.…”
Section: Assessment Of the Impact Of The Agricultural Production Fact...mentioning
confidence: 65%
“…Higher doses of nitrogen fertilization had a positive effect on all elements of the yield structure, increasing the number of ears, ear fertility, and grain abundance. It was also confirmed by the results of numerous studies, which indicate that long-term N fertilization can contribute to relieving the global food crisis by not only enhancing cereal yield, but also promoting its stability [44,45]. Mohammed et al [46] also observed the beneficial effect of an increase in fertilizer N rates in wheat grain yield and protein content.…”
Section: Assessment Of the Impact Of The Agricultural Production Fact...mentioning
confidence: 65%
“…Our results showed higher average protein concentration in wheat under all treatments regardless yield differences with triticale. Increases in grain protein concentration without changes in grain yield is commonly observed in wheat N fertilization trials ( Walsh et al, 2020 ) with negative implications for NUE ( Walsh et al, 2022 ). Conceptually, increasing yield and NUE in wheat would only be achieved at the expense of grain protein concentration ( Barraclough et al, 2010 ) which is not desirable for the baking industry.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of color indices to the grain yield is mainly based on the dependence of this yield on the nitrogen content [3,4,38,107,109], which plays a key role in the grain formation and is strongly related to color parameters (see Section 4.1 and Table 2). Additionally, the nitrogen content influences the grain quality and nutritional value [144,145], i.e., these characteristics can also be related to color parameters. Vollmann et al [53] showed that R and G are moderately and negatively related to protein and oil content in soybean seeds (R 2 is about 0.45-0.65); in contrast, B is positively correlated with these characteristics (R 2 is about 0.45-0.62) (see Table 2 for details).…”
Section: For Detail)mentioning
confidence: 99%